Psychological Contract Breach, Behavioural Work Outcomes, Organisational Identification, and Islamic Work Ethics: A Moderated Mediation Study - Monir Hamatto EL-Ghorra (Ziane Achour University of Djelfa, 2021)
We investigated how organisational identification (OID) mediates the influences of psychological contract breach (PCB) on two work outcomes [organisational citizenship behaviour (OCB) and counterproductive work behaviour (CWB)], and how Islamic work ethics (IWE) moderated the PCB–OID relationship. We collected data from 256 Palestinian managers in Gaza Strip ministries using a self-report questionnaire; we employed Structural Equation Modelling in analysing the data using Smart PLS. Our findings reveal that OID mediates between PCB and the two work outcomes. Further, we show that IWE has no moderating influence on the PCB–OID relationship. Finally, the influence of PCB on the two work outcomes is insignificant.